IMPLEMENTASI PERATURAN BUPATI TENTANG PENGURANGAN PENGGUNAAN PLASTIK DI KABUPATEN BANTAENG - Saleh, Citra Puspita; Setiawati, Budi; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to find out the implementation of the district head's regulations in reducing the use of plastic in Bantaeng Regency. This study used qualitative research. Informants in this study used five people. The research data was collected through observation, interviews, and documentation. The results showed that the implementation of the Regent's Regulation on Reducing the Use of Plastic in Bantaeng Regency had not been effective in terms of financial resources that were still limited so that the allocation of funds for facilities and infrastructure was still lacking, such as the lack of available garbage trucks, so that the accumulation of plastic waste still occurred frequently. On the other hand, although guidance and counseling had been held on how to reduce the use of plastic and manage plastic waste through 3R (Reuse, Reduce, Recycle) which was carried out by the Environmental Service in collaboration with retail entrepreneurs and sub-districts in Bantaeng Regency. But it all came back to the awareness and concern of each individual in preserving the environment. The level of public concern for the environment was still low.